Delivery room oxygen titration strategies for resuscitation of preterm infants - Sotiropoulos, James X.; Soll, Roger F.; Fiander, Michelle; Bruschettini, Matteo ; 0000-0002-4775-872X; Oei, Ju Lee; Kapadia, Vishal; Seidler, Anna Lene (The Cochrane database of systematic reviews, 2025)
OBJECTIVES: This is a protocol for a Cochrane Review (intervention). The objectives are as follows: Research objective 1: to assess the effects of different oxygen saturation targets for the delivery room resuscitation of preterm infants. Research objective 2: to assess the effects of different titration strategies for the delivery room resuscitation of preterm infants.